The research in to passengers’ transportation by land transport and the formation of formalized models - Butkevičius, Jonas; Žvirblis, Algis (Transport, 2003)
The analysis of the Lithuanian passengers’ Transportation market has been carried out as well as the analysis of passengers’Transportation by land transport, on the basis of which the most important problems causing areas of local, intercity as well as international Transportation have been identified. Systematically evaluating passengers’ Transportation market on the city’s scale as well as the complex character of passengers’ Transportation by urban public transport, formalized models enabling us to solve the entire complex of tasks related to the problems of passengers’ Transportation have been worked out. Identifying a necessary summative effect in terms of social and economic factors a model for railway transport market which would correspond to that market specificity has been formed. These models can be employed to carry out the calculations needed to determine internal and international routes. First Published Online: 19 Dec 2011